High-dose flecainide with low-dose β-blocker therapy in catecholaminergic polymorphic ventricular tachycardia: A case report and review of the literature. Issue 1 (January 2015) - Steinfurt, Johannes; Dechant, Markus-Johann; Böckelmann, Doris; Zumhagen, Sven; Stiller, Brigitte; Schulze-Bahr, Eric; Bode, Christoph; Odening, Katja E.
Abstract: Background: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is characterized by recurrent syncopes and sudden cardiac death triggered by sympathetic activation in young individuals without structural heart disease and a normal baseline electrocardiogram. There is reason to question whether the current expert consensus treatment recommendation, maximal tolerated β-blockade alone or in combination with low-dose flecainide, is the optimal antiarrhythmic treatment strategy in CPVT, as high doses of β-blockers may eventually lead to adverse side effects and β-blocker discontinuation. Indeed, β-blocker non-compliance accounts for around 5% of sudden cardiac deaths in CPVT patients. Case report: Differing from the current recommendation, we present the first report of a CPVT patient successfully treated with high-dose flecainide and minimal β-blockade. This combination resulted in complete suppression of ventricular arrhythmias during exercise stress tests and Holter monitoring and was well tolerated without any side effects. We review the current literature on β-blocker non-compliance-related sudden cardiac death in CPVT, summarize the in vitro and in vivo data on flecainide therapy in CPVT, and discuss the rationale of our antiarrhythmic approach. <Learning objective: This case illustrates typical features of CPVT including the therapeutic management of a young CPVT patient with poor β-blocker tolerance at normal dosages. In this setting, high-dose flecainide combined with minimal β-blockade may (1) result in complete antiarrhythmic response and may (2) improve the antiarrhythmic drug-compliance thereby reducing the risk of non-compliance-related sudden cardiac death.>